A utilização dos gráficos Shewhart e EWMA no monitoramento estatístico de indicadores de desempenho hospitalar em uma maternidade pública na cidade de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
In the current context, the use of indicators and information to support the planning of public policies to monitor health organizations for improvement and monitoring of the management process is intensified. In the search for better results in these organizations, it is proposed to present the feasibility in the use of Shewhart and EWMA statistical control charts in the monitoring of hospital indicators, as a tool to aid decision-making in the Alvorada public maternity hospital in the city of Manaus, to detect Changes in various types of processes. In this dissertation, the Shewhart and Exponentially Weighted Moving Average (EWMA) charts were used to monitor the evolution of three hospital quality indicators: Hospital Occupancy Rate, Hospital Infection Rate, and Newborn Rate with Some Pathology, available from the Dawn Maternity Manaus in the period from 2010 to 2014. To meet the general objective, the following specific objectives were defined; To describe the indicators of hospital performance provided by the selected maternity hospital, to estimate the parameters of the proposed control charts and to analyze their performance in the monitoring of the maternity process. Initially, a descriptive analysis of the data was performed, in addition to the tests to verify the normality and independence assumptions required by the traditional Shewhart and EWMA charts, which will be the subject of the study. After indicating the parameters that are necessary for the construction of the graphs, all points within the control limit for the analyzed rates were observed, ie all the rates were stable for both graphs. By observing the graphs, the advantage of the EWMA chart was detected in early detection of changes in the process, besides being able to identify changes of smaller magnitude, thus providing a corrective action with greater speed. The use of these graphs is a very efficient resource in management for process control and decision making, due to the large number of variables that could be controlled in a hospital environment, or in any other sector related to people's health, thus bringing about improvements In other sectors, such as personal, family and professional.
Keywords: Gráficos de Controle; Indicadores de Desempenho; Epidemiologia; Maternidade; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO